Relationship between the engaging force of planetary gear train and the position‐correlated modal properties. Issue 13 (7th December 2018) - Zhang, Keming; Zhang, Luke; Shao, Yimin; Xiao, Huifang; Xu, Jin; He, Rong; Li, Liang; Li, Hongwu
Abstract : Planetary gear train (PGT) is widely used in a variety of fields such as helicopters and aircraft engines. The failure of meshing gear often happens in the PGT due to the working condition of high speed, variable load, high‐frequency excitation, assembly error etc. However, the causes of gear failure are still insufficiency, especially in the condition of high speed and high‐frequency excitation. In this work, the engaging force between gear meshing pair of the PGT under high‐frequency excitation is studied using the proposed position‐correlated modal properties calculation method, which is established by incorporating the effect of meshing position and meshing phase difference of each contact pair into the free vibration model to study the modal properties of the PGT at different meshing positions. The corresponding engaging force responses based on the position‐correlated modal properties are investigated. The simulation results show that the higher‐order natural frequencies of the system are greatly affected by the meshing position. The peaks of engaging force occur at meshing positions where the natural frequencies are equal to the excitation frequency, which can be the potential cause of the gear damage.